Butyrate and retinoic acid imprint mucosal-like dendritic cell development synergistically from bone marrow cells. (13th June 2017) - Qiang, Y; Xu, J; Yan, C; Jin, H; Xiao, T; Yan, N; Zhou, L; An, H; Zhou, X; Shao, Q; Xia, S
Summary: Accumulating data show that the phenotypes and functions of distinctive mucosal dendritic cells (DCs) in the gut are regulated by retinoic acid (RA). Unfortunately, the exact role of butyrate in RA-mediated mucosal DC differentiation has not been elucidated thoroughly to date. Mucosal-like dendritic cell differentiation was completed in vitro by culturing bone marrow cells with growth factors [granulocyte–macrophage colony-stimulating factor (GM-CSF/interleukin (IL)-4], RA and/or butyrate. The phenotypes, cytokine secretion, immune functions and levels of retinal dehydrogenase of different DCs were detected using quantitative polymerase chain reaction (qPCR), enzyme-linked immunosorbent assay (ELISA) and flow cytometry, respectively. The results showed that RA-induced DCs (RA-DCs) showed mucosal DC properties, including expression of CD103 and gut homing receptor α4 β7, low proinflammatory cytokine secretion and low priming capability to antigen-specific CD4 + T cells. Butyrate-treated RA-DCs (Bu-RA-DCs) decreased CD11c, but increased CD103 and α4 β7 expression. Moreover, the CD4 + T priming capability and the levels of retinal dehydrogenase of RA-DCs were suppressed significantly by butyrate. Thus, butyrate and retinoic acid have different but synergistic regulatory functions on mucosal DC differentiation, indicating that immune homeostasis in the gut depends largely upon RA and butyrate to imprint different mucosal DC subsets, both individually and collectively. Graphical Abstract: